A novel CDK7 inhibitor of the Pyrazolotriazine class exerts broad-spectrum antiviral activity at nanomolar concentrations - Hutterer, Corina; Eickhoff, Jan; Milbradt, Jens; Korn, Klaus; Zeitträger, Isabel; Bahsi, Hanife; Wagner, Sabrina; Zischinsky, Gunther; Wolf, Alexander; Degenhart, Carsten; Unger, Anke; Baumann, Matthias; et al. (Antimicrobial Agents and Chemotherapy, 2015)
Protein kinases represent central and multifunctional regulators of a balanced virus-host interaction. Cyclin-dependent protein kinase 7 (CDK7) plays crucial regulatory roles in cell cycle and transcription, both connected with the replication of many viruses. Previously, we developed a CDK7 inhibitor, LDC4297, that inhibits CDK7 in vitro in the nano-picomolar range. Novel data from a kinome-wide evaluation (>330 kinases profiled in vitro) demonstrate a kinase selectivity. Importantly, we provide first evidence for the antiviral potential of the CDK7 inhibitor LDC4297, i.e., in exerting a block of the replication of human cytomegalovirus (HCMV) in primary human fibroblasts at nanomolar concentrations (50% effective concentration, 24.5 ± 1.3 nM). As a unique feature compared to approved antiherpesviral drugs, inhibition occurred already at the immediate-early level of HCMV gene expression. The mode of antiviral action was considered multifaceted since CDK7-regulated cellular factors that are supportive of HCMV replication were substantially affected by the inhibitors. An effect of LDC4297 was identified in the interference with HCMV-driven inactivation of retinoblastoma protein (Rb), a regulatory step generally considered a hallmark of herpesviral replication. In line with this finding, a broad inhibitory activity of the drug could be demonstrated against a selection of human and animal herpesviruses and adenoviruses, whereas other viruses only showed intermediate drug sensitivity. Summarized, the CDK7 inhibitor LDC4297 is a promising candidate for further antiviral drug development, possibly offering new options for a comprehensive approach to antiviral therapy.
EVALuna2:8274